Benedetta Fantaci - Influence of Mechanical Properties on Photorefractive Keratectomy OutCome - Fantaci, Benedetta (Jornada de Jóvenes Investigadores del I3A, 2022)
INFLUENCE OF MECHANICAL PROPERTIES ON PHOTOREFRACTIVE KERATECTOMY OUTCOME